IMPLEMENTATION OF THE K-NEAREST NEIGHBOR METHOD FOR AN EQUIPMENT INVENTORY SYSTEM AT THE XYZ CITY FIRE AND DISASTER MANAGEMENT DEPARTMENT - Dafa Arya Wijaya; Febie Elfaladonna; Meivi Kusnandar; Deri Darfin; Devi Sartika (Politeknik META Industri Cikarang, 2026)
Background Inventory management is essential for ensuring the availability, traceability, and proper maintenance of organizational assets. However, the XYZ City Fire and Disaster Management Department still manages inventory using Microsoft Excel, resulting in inefficient data processing, limited accessibility, and a high risk of data entry errors. Purpose This study aims to develop a web-based inventory management system integrated with the K-Nearest Neighbor (KNN) algorithm to improve inventory management efficiency and automatically evaluate equipment feasibility. Methodology A web-based inventory application was developed to manage inventory records and classify equipment conditions using the K-Nearest Neighbor (KNN) method. System performance was evaluated using classification metrics, including accuracy, precision, recall, and F1-score. Findings The developed system successfully automated inventory management and equipment feasibility assessment. Experimental results showed that the KNN model achieved 100% accuracy, precision, recall, and F1-score, demonstrating its effectiveness in classifying equipment as either suitable for continued use or requiring replacement. Implications The proposed system provides a practical solution for improving inventory management by increasing data accuracy, accelerating decision-making, and supporting real-time monitoring of equipment conditions. Although the system performed exceptionally well in this study, further validation using larger and more diverse datasets is recommended to evaluate its scalability and generalizability.. Originality This study integrates a web-based inventory management system with the K-Nearest Neighbor algorithm to automate equipment feasibility evaluation in a fire and disaster management agency, providing an accurate, efficient, and real-time decision-support tool for inventory management.